Surface Formation and Degradation of Cathode Active Materials during Synthesis and Battery Operation - Dreyer, Sören Lukas; Justus Liebig University Giessen (My University, 2024)
Lithium-ion batteries (LIBs) offer both a relatively high energy and high power density, and thus see widespread application and continuous research and development efforts, especially to increase their energy density further and to decrease their cost. Sodium-ion batteries (SIBs) are considered, both in research and industry, as a complementary battery technology to LIBs, with on the one hand lower energy densities, yet on the other hand with lower costs, due to the ubiquity of sodium in contrast to the relative scarcity of lithium. In both LIBs and SIBs, the cathode active material (CAM) makes up the largest part each of battery weight and cost. Consequently, understanding and improving CAMs is of utmost importance to further develop battery technology. This work focusses on the CAM surface from various perspectives, with in situ gas evolution studies as an additional bridging element, as various reactions on and of the CAM surface can be understood from the gasses they evolve. First, a review of in situ gas evolution studies on battery materials is presented, focusing on novel materials and cell concepts. The gas evolution of SIBs in contrast to LIBs is identified as a research gap. The first original research work in this thesis then considers the formation of CAM surfaces in dependence of the process route of CAM preparation. Specifically, it is shown that Zr4+, when introduced into LiNiO2 (LNO) as a dopant, is enriched on the primary particle grain boundaries, acting as a grain growth inhibitor. The doping process route determines the initial Zr4+ distribution, and thus the extent of the grain growth inhibition, yielding LNO primary particles of different specific surface areas. This in turn determines both electrochemical performance and gas evolution of the CAM. In a second work, the exposure of new surfaces due to crack formation during bat-tery cycling is studied operando via Acoustic Emission (AE) for a series of SIB CAMs with increasing configurational entropy. It is shown that AE allows to distinguish be-tween less degradative intergranular cracking, i.e. deagglomeration of particles, and more degradative intragranular cracking, while not being sensitive to gas evolution. Lastly, the gas evolution of Prussian white (PW), a SIB CAM, especially the evolution of (CN)2 and HCN from its hexacyanoferrate structure, is studied in detail, after a previous study finding first evidence for (CN)2 evolution, indicating a new surface degradation mechanism for PW CAMs. It is found that the CAM water content de-termines the evolution of H2, which is the most prominently evolved gas. Yet, the conductive salt anion in the electrolyte determines CO2 and (CN)2 evolution between NaPF6- and NaClO4-based electrolytes. The oxidative properties of NaClO4 are identified as the cause for increased (CN)2 evolution in its presence at the CAM surface, and a plausible reaction mechanism is presented in light of the available literature.
Oberflächenentstehung und Degradation von Kathodenaktivmaterialien während Synthese und Batteriebetrieb
Keywords: ddc:540